C‐reactive Protein in HPV‐Positive and HPV‐Negative Oropharyngeal Cancer. (18th September 2018) - Johnson‐Obaseki, Stephanie; Caulley, Lisa; Corsten, Martin; Liu, Geoffrey; Dimitroulakos, Jim; Goldstein, David; Irish, Jonathan; Rider, Jennifer
Abstract : Objective: Evaluate serum C‐reactive protein (CRP) in human papillomavirus (HPV)–positive oropharynx cancer as compared with HPV‐negative oropharynx cancer and determine if CRP levels were associated with overall survival and/or recurrence‐free survival. Study Design: Prospective cohort study. Setting: Tertiary care academic cancer center between 2007 and 2010. Subjects and Methods: Among patients with oropharynx cancer and confirmed HPV status, plasma CRP levels were measured with a high‐sensitivity ELISA kit. Multivariable logistic regression analysis compared 4 categories of CRP (low, moderate, high, very high) between the HPV‐positive and HPV‐negative groups. Kaplan‐Meier methods and Cox regression models were used to determine overall survival and recurrence‐free survival by CRP level in both populations. Results: Between 113 HPV‐positive and 110 HPV‐negative patients, CRP levels were significantly higher in the HPV‐positive group, but these levels did not demonstrate a statistically significant dose‐response trend. Higher CRP levels were also associated with reduced overall survival ( P =. 016) and recurrence‐free survival ( P <. 001) within the HPV‐negative group in univariable analysis; in multivariate analysis, the comparisons were not significantly different. Within HPV‐positive oropharynx cancer, CRP levels were not significantly associated with overall survival or recurrence‐free survival in univariable or multivariable analyses. Conclusion: Circulating CRP was higher in HPV‐positive versus HPV‐negative oropharynx cancer. Among HPV‐negative patients, higher CRP levels were associated with reduced survival.